Multi-mycotoxin determination in coffee beans marketed in Tunisia and the associated dietary exposure assessment. (October 2022) - Oueslati, S.; Ben Yakhlef, S.; Vila-Donat, P.; Pallarés, N.; Ferrer, E.; Barba, F.J.; Berrada, H.
Abstract: Coffee is an agricultural product highly susceptible to mycotoxin contamination. The present study evaluates the natural presence of 17 mycotoxins in different types of coffee sampled in Tunisia (n = 100), by using liquid chromatography-tandem mass spectrometry methods (LC-MS/MS). The results showed that all the analyzed samples were contaminated by at least one mycotoxin. Tentoxin (TENT) was registered in 95 samples with maximum of 300 μg/kg while aflatoxin B1 (AFB1) and ochratoxin A (OTA) in 7 and 18 samples, respectively. Most of OTA positive samples exceeded the OTA maximum regulatory limit (MRL). The highest levels of OTA, aflatoxin G1 (AFG1), and alternariol monomethyl ether (AME) levels were detected in Arabica samples reaching up to 122.6; 186.9 and 388.6 μg/kg, respectively. 82 samples were contaminated by at least two mycotoxins and up to nine different mycotoxins co-occurred simultaneously in two samples. The dietary exposure of the Tunisian population was also assessed, and the probable daily intake (PDI) ranged between 0.27– 1.48 and 2.79–5.28 ng/kg bw/day for OTA and zearalenone (ZEN), respectively. It was also found that, at the worst scenario (Mp), consumers may be reaching up to 2.1% and 8.7% of the tolerable daily intakes (TDIs) of ZEN and OTA, respectively. However, no toxicological risk arises to most of the analyzed mycotoxins from the regular consumption of the evaluated coffee. Highlights: 11 of 17 analyzed mycotoxins were detected in different types of coffee marketed in Tunisia. Co-occurrence from 2 to 9 mycotoxins was observed in 82% of analyzed samples. The contaminated samples showed high levels of TENT, AFG1 and AFG2 (from 9.4 to 300.5 μg/kg). 17 of 18positive samples for OTA exceeded the maximum levels established. Consumers may be reaching up to 2.1% and 8.7% of the tolerable daily intakes (TDIs) set for ZEN and OTA, respectively.